Almond intake alters the acute plasma dihydroxy-octadecenoic acid (DiHOME) response to eccentric exercise - Nieman, David C.; Omar, Ashraf M.; Kay, Colin D.; Kasote, Deepak M.; Sakaguchi, Camila A.; Lkhagva, Ankhbayar; Weldemariam, Mehari Muuz; Zhang, Qibin (Frontiers in Nutrition, 2023)
Introduction This investigation determined if 4-weeks ingestion of nutrient-dense almonds mitigated post-exercise inflammation and muscle soreness and damage. Methods An acute 90-min of eccentric exercise (90-EE) was used to induce muscle damage in 64 non-obese adults not engaging in regular resistance training (ages 30–65 years, BMI < 30 kg/m2). Using a parallel group design, participants were randomized to almond (AL) (57 g/d) or cereal bar (CB) (calorie matched) treatment groups for a 4-week period prior to the 90-EE (17 exercises). Blood and 24-h urine samples were collected before and after supplementation, with additional blood samples collected immediately post-90-EE, and then daily during 4 additional days of recovery. Changes in plasma oxylipins, urinary gut-derived phenolics, plasma cytokines, muscle damage biomarkers, mood states, and exercise performance were assessed. Results The 90-EE protocol induced significant muscle damage, delayed onset of muscle soreness (DOMS), inflammation, reduced strength and power performance, and mood disturbance. Interaction effects (2 group × 7 time points) supported that AL vs. CB was associated with reduced post-exercise fatigue and tension (p = 0.051, 0.033, respectively) and higher levels of leg-back strength (p = 0.029). No group differences were found for post-90-EE increases in DOMS and six cytokines. AL was associated with lower levels of serum creatine kinase immediately- and 1-day post-exercise (p = 0.034 and 0.013, respectively). The 90-EE bout increased plasma levels immediately post-exercise for 13 oxylipins. Interaction effects revealed significantly higher levels for AL vs. CB for 12,13-DiHOME (p < 0.001) and lower levels for 9,10-DiHOME (p < 0.001). Urine levels increased in AL vs. CB for seven gut-derived phenolics including 5-(3′,4′-dihydroxyphenyl)-γ-valerolactone that was inversely related to changes in plasma 9,10-DiHOME (r = −0.029, p = 0.021). Discussion These data support some positive effects of almond intake in improving mood state, retaining strength, decreasing muscle damage, increasing the generation of gut-derived phenolic metabolites, and altering the plasma oxylipin DiHOME response to unaccustomed eccentric exercise in untrained adults. The elevated post-exercise plasma levels of 12,13-DiHOME with almond intake support positive metabolic outcomes for adults engaging in unaccustomed eccentric exercise bouts.